If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x(x + -6) + 9 = 25 Reorder the terms: x(-6 + x) + 9 = 25 (-6 * x + x * x) + 9 = 25 (-6x + x2) + 9 = 25 Reorder the terms: 9 + -6x + x2 = 25 Solving 9 + -6x + x2 = 25 Solving for variable 'x'. Reorder the terms: 9 + -25 + -6x + x2 = 25 + -25 Combine like terms: 9 + -25 = -16 -16 + -6x + x2 = 25 + -25 Combine like terms: 25 + -25 = 0 -16 + -6x + x2 = 0 Factor a trinomial. (-2 + -1x)(8 + -1x) = 0Subproblem 1
Set the factor '(-2 + -1x)' equal to zero and attempt to solve: Simplifying -2 + -1x = 0 Solving -2 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + -1x = 0 + 2 Combine like terms: -2 + 2 = 0 0 + -1x = 0 + 2 -1x = 0 + 2 Combine like terms: 0 + 2 = 2 -1x = 2 Divide each side by '-1'. x = -2 Simplifying x = -2Subproblem 2
Set the factor '(8 + -1x)' equal to zero and attempt to solve: Simplifying 8 + -1x = 0 Solving 8 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-8' to each side of the equation. 8 + -8 + -1x = 0 + -8 Combine like terms: 8 + -8 = 0 0 + -1x = 0 + -8 -1x = 0 + -8 Combine like terms: 0 + -8 = -8 -1x = -8 Divide each side by '-1'. x = 8 Simplifying x = 8Solution
x = {-2, 8}
| 10.2+3n=11 | | X+.05x=294000 | | 10y-7=4y+5 | | -84=-2+6x+8+3x | | -7b=63 | | 2(u-2)-5u=-2(u+3) | | 4a=2a+1 | | 4x+5x+3+5x+6=107 | | 5x-9=87-7x | | 4x+2y+3z= | | 0=14x^2+x-4 | | 2x^2+48x+160=364 | | 10(z+3)-3(z-3)=2(z-1)+4(z-4) | | 28x-7-16x=3(4x-3)+2 | | ln(x+10)-ln(x+4)=3 | | -1/5×-9/7=-3/2 | | 96-33-(-109)= | | 6=-3(22-y)+2(y-4) | | 83-(6x+15)=6(x+7)+x | | in(x+10)-in(x+4)=3 | | 5a+7y+8a+7y= | | 2x^3+5x^2+x+3=621 | | 4x+5x+2+5x+7=107 | | 2x^3+5x^2+x-618=0 | | 2x^2+17x+130=0 | | -5/8×1/4 | | f(x)=7x-8/9 | | 3X+23X=27 | | X+72+(x+2)=180 | | 12=w-3 | | x+1.536585366y=31.64165854 | | -4v-32=0 |